Reliability and Validity of the Adult Hope Scale among Nursing Home Residents with and without Cognitive Impairment. Issue 3 (3rd May 2020) - DiGasbarro, Diana; Midden, Allison; Van Haitsma, Kimberly; Meeks, Suzanne; Mast, Benjamin
ABSTRACT: Objectives : The current study aims to examine the reliability and validity of the Adult Hope Scale among older adults with and without cognitive impairment who were recently admitted to a nursing home. Methods : Sixty-four recently admitted nursing home residents, 32 of whom had cognitive impairment, were administered the Adult Hope Scale and measures of concurrent and divergent validity. Results : In this sample, the Adult Hope Scale demonstrated good to excellent reliability. The Adult Hope Scale also correlated as expected with measures of concurrent and divergent validity, thus supporting the validity of the scale to measure hope in older adults despite level of cognitive functioning. Conclusions : This study shows that the Adult Hope Scale is a reliable and valid measure of hope in this sample of older adults with and without cognitive impairment who were recently admitted to a nursing home. Given the small sample size, additional research on the psychometric properties of the utility of the Adult Hope Scale in older adults with and without cognitive impairment is warranted. Clinical Implications : These preliminary findings allow future researchers and clinicians to consider administration of the Adult Hope Scale to individuals with and without cognitive impairment living in long-term care facilities. Gathering additional data on the psychometrics of this measure will enable new directions in research involving self-report measures for older adults with cognitive impairment, and in the development of interventions involving hope to improve physical and mental health in long-term care residents.